History of Jami' Mosque Air Tiris: Cultural Symbol of Kampar Religious Tourism Destination as Serambi Mecca in Riau - Roza, Ellya; Pama, Violeta Inayah; Fuadi, M. Fadhil; Pama, Sindi Ayudia; bin Nik Hasan, Nik Abdul Rakib bin (Lembaga penelitian dan pengabdian kepada Masyarakat, 2023)
This article aims to describe the propriety of the Jami' Air Tiris Mosque as a cultural symbol of a religious tourism destination in Kampar Regency and the embodiment of Kampar as the porch of Mecca, Riau. This is because Kampar's nickname as the porch of Mecca, Riau has taken root and developed everywhere, so it really needs proof by realizing the slogan with reality. The method used is through a qualitative approach that leads to content analysis. The results found that based on Law no. 10 of 2009, Chapter 1, Article 1 it has been stated that tourism is a variety of tourism activities and is supported by various facilities and services provided by the community, businessmen, government and local government. Then it was strengthened by Regional Regulation number 6 of 2016 concerning the Formation and Composition of Regional Apparatuses of Kampar Regency, then in chapter II article 3 it is stated that the Tourism and Culture Office which carries out Government affairs in the field of tourism and culture includes organizing religious tourism which has the connotation of travel activities carried out voluntarily to enjoy tourist objects and attractions in a religious tourist destination. In this case, it is the Jami' Mosque in Air Tiris which basically can be used as a religious tourism destination in Kampar Regency because several conditions are determined to become a religious tourism destination that have fulfilled and are included in such levels as (1) destination and accessibility aspects; (2) aspects of amenities and buildings; (3) aspects of attractions and storytelling; (4) aspects of information through social media and technology. The conclusion is that the Jami' Mosque can become a symbol of Riau Province in general and Kampar in particular as the porch of Riau's Mecca because already has religious tourism as physical evidence and not just a slogan